Konsep An-Nubuwwah dalam Diskursus Filsafat - Juwaini Juwaini; Aminuddin Aminuddin (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2011)
This paper attempts to search about an-Nubuwwah concept put forward by the hilosophers of Islam. Exposure is considered important because an-Nubuwwah issue is basically a model of philosophical understanding of religion as an object, a conclusion to the design and construction of philosophical thought the concept of that has been formulated and defended from the attacks of al-Razi. According to philosophers, is an illustration of the people who do not believe in the existence of prophethood. The teori of an-Nubuwwah in the present era can be alternative solutions to address some essential issues in human life which has not been able answer and resolve the general psychology. This discussion is also necessary to study more deeply in order to find a clear format that can be universally accepted. Islamization of knowledge is something that is absolute existence to prevent us from the path of religion.